1998
DOI: 10.1046/j.1471-4159.1998.71062565.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Uptake at the Blood‐Brain Barrier Is Mediated by N‐System Transport

Abstract: Abstract:The mechanism of unidirectional transport of glutamine from blood to brain in pentobarbital-anesthetized rats was examined using in Situ perfusion. Amino acid uptake into brain across the blood-brain barrier (BBB) is classically thought to be via the Na-independent large neutral (L-system), acidic and basic amino acid transporters. In the presence of physiological concentrations of amino acids in the perfusate, which should saturate the known amino acid transporters at the BBB, the cortical transfer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…The second part examined the effects of the same model of cerebral ischemia on CP function and BBB function by measuring blood to CP and blood to brain L-[ 14 C]glutamine transport. Glutamine transport at both the CP and the BBB is Na + -dependent and, therefore, inhibited by ischemiainduced changes in intracellular Na + concentration (Keep and Xiang, 1995;Ennis et al, 1998;Kawai et al, 1999). Rats were either exposed to 10, 30, or 70 mins of permanent 2VO + hypotension or 10 mins of ischemia with 60 mins of reperfusion or 30 mins of ischemia + 40 mins of reperfusion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second part examined the effects of the same model of cerebral ischemia on CP function and BBB function by measuring blood to CP and blood to brain L-[ 14 C]glutamine transport. Glutamine transport at both the CP and the BBB is Na + -dependent and, therefore, inhibited by ischemiainduced changes in intracellular Na + concentration (Keep and Xiang, 1995;Ennis et al, 1998;Kawai et al, 1999). Rats were either exposed to 10, 30, or 70 mins of permanent 2VO + hypotension or 10 mins of ischemia with 60 mins of reperfusion or 30 mins of ischemia + 40 mins of reperfusion.…”
Section: Methodsmentioning
confidence: 99%
“…14 C]glutamine transport since such transport at the CP and the BBB is Na + -dependent (Keep and Xiang, 1995;Ennis et al, 1998). The use of this marker allowed assessment of CP injury during the short ischemic period as well as during reperfusion.…”
Section: Morphologic and Methodological Considerationsmentioning
confidence: 99%
“…This value is considerably higher than Table 1. Concentrations (mmol/L) and 13 C enrichments (%) of plasma and brain amino acids during intravenous [U- 13 Glutamine transport in mouse brain P Bagga et al previously reported rates of glutamine influx for physiologic plasma glutamine concentrations (0.42 to 0.48 mmol/L) of 0.0049 mmol/g per minute 26 or 0.0041 mmol/g per minute in parietal cortex 23 as measured with L-[ 14 C]glutamine and in situ carotid artery perfusion. However, under physiologic condition, several amino acids present in blood may compete with glutamine for transport, effectively raising the apparent plasma concentration required for half maximal transport, K m ', and reducing its influx as much as 22-fold.…”
Section: Comparison Of Glutamine Influx With Previously Reported Valuesmentioning
confidence: 99%
“…First, glutamine transport between blood and brain involves several transporter proteins, all of which belong to one or more families of large neutral amino-acid transporters. 26,[38][39][40] Glutamine transport into brain and cerebrospinal fluid from the blood involves both System N, A and L-like transporters, and within brain parenchyma, glutamine transport into neurons and astrocytes involves mainly systems-A and N transporter proteins, respectively. Because the present study involved bulk cortical tissue measurements of glutamine and glutamate, and consequently did not differentiate between the different neural compartments, the measured value of V Gln(in) must reflect an average of all the different transporter isoforms mediating cortical glutamine uptake and metabolism.…”
Section: Limitations Of the Study And Other Observationsmentioning
confidence: 99%
“…In addition, early in vivo studies by Oldendorf and others (reviewed in the study by Smith et al (1987)) measured a low but significant brain uptake for glutamine that was attributed to a neutral AA carrier system. Later, Ennis et al (1998) showed a Na + -dependent, pH-sensitive glutamine luminal transport that was fully inhibited by histidine but not by cystine (system A or ASC inhibitors) or 2-aminobicyclo-(2,2,1)-heptane-2-carboxylic acid (BCH) (system L inhibitor) and therefore identified as system N. In addition to our present report showing Snat3 protein expression, our previous study additionally found a robust and regulated gene Snat1 is localized on the luminal membrane of brain vasculature, but not on BBB capillaries. Fresh PFA-fixed mouse brain tissue sections were imaged by confocal microscopy after staining with anti-Snat1 (green) and anti-Glut1 (blue) antibody; the endothelial nucleus is indicated as '*' and pericyte as 'P'.…”
Section: Potential Roles Of Snat1 and Snat3 In The Cerebral Vasculaturementioning
confidence: 98%